Antenatal care by Bidan Delima in Pekanbaru - Susanti, Ari; Fadmiyanor, Isye (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2020)
Abstract One of the healthworker who are competent in providing antenatal cara is amidwife. Association of indonesian midwive launching Bidan Delima Program to make midwife more professional. This research aim to obtain information aboutantenatal care by bidan delima in Pekanbaru. This research was qualitativeresearch with phenomenalogical approach. The informan are Facilititator ofbidan delima, woman who perform antenatal care to bidan delima, also bidandelima who selected by purposive sampling. Data collected with deep interviewand checking documentation which is conducted by bidan delima. Data wereanalysis by source and technic triangulation. The result show there is a midwifewho proovide TT imunization without rate imunization status. Bidan delimacommonly did not have kit or tool to examine blood gr Hepatitis Boup, HIV,Sifilis dan. We expected bidan delima service unit organize training/ workshoopto upgrade bidan delima knowledge about antenatal care